The European Approach to Propaganda confronted with the Realities of Colonial Africa - Vincent Bouchard (Mise au Point)
Through the comparison of the choices and the difficulties encountered by the British, Belgian and French colonizers when setting up propaganda systems, this article aims to define a transnational conception of the cinematographic medium. Indeed, the syntheses of the propaganda systems set up in Europe and the reports on the experiments carried out in the colonies reveal a number of recurring preconceptions: cinema as a vector of universally decipherable messages; cinema as a form of direct access to the viewer’s subconscious; cinema as a form of expression of a “European technological superiority”.